FACTORS FOR DEVELOPING THE CREATIVE ACTIVITY OF FUTURE PRIMARY SCHOOL TEACHERS IN A DIGITAL EDUCATIONAL ENVIRONMENT - Ulugbek Navruzov (Modern American Journals, 2025)
The article analyzes the factors that contribute to the development of creative activity among future primary school teachers in the context of a digital educational environment. The rapid integration of digital technologies into teacher education requires future educators not only to master technical tools but also to develop creative and innovative thinking. Creativity is a crucial component of pedagogical competence, allowing teachers to design engaging learning experiences, adapt to new teaching situations, and inspire students’ intellectual curiosity. The study identifies key psychological, pedagogical, and technological factors influencing creative development, including digital literacy, motivational readiness, collaborative learning, and reflective practice. It also emphasizes the role of digital platforms, multimedia tools, and project-based learning in stimulating creative potential. Based on the analysis, recommendations are made for enhancing the structure of teacher education programs, integrating digital creativity modules, and fostering an environment conducive to experimentation, collaboration, and self-expression. The findings underscore the importance of combining pedagogical knowledge with digital fluency to prepare future teachers capable of functioning effectively and creatively in the modern digital classroom.
Keywords: Creative activity, digital education, teacher training, primary education, innovation, digital competence, pedagogical creativity, professional development, interactive learning, educational technology.